Seminonparametric Estimation of Conditionally Constrained Heterogeneous Processes: Asset Pricing Applications - Gallant, A. Ronald; Tauchen, George (Econometrica, 1989)
A. Ronald Gallant, George Tauchen, Seminonparametric Estimation of Conditionally Constrained Heterogeneous Processes: Asset Pricing Applications, Econometrica, Vol. 57, No. 5 (Sep., 1989), pp. 1091-1120